Debris Flows in Mining Areas: Risk Assessment and Mitigation Strategies for Mine Waste Management - B. Goswami (International Journal of Minerals, 2024)
This study investigates the dynamics and risks associated with debris flows, focusing on the differentiation between natural and mine-generated debris, particularly in storm-affected areas. Mine debris flows, frequently exacerbated by heavy rainfall and human activities, are a major concern due to their destructive potential and environmental impact. The research highlights key factors contributing to debris flow hazards, such as sediment composition, flow velocity, and terrain susceptibility. Additionally, the study explores the application of numerical simulation models for assessing debris flow height, runout distance, and momentum exchange between solid and fluid components. Findings demonstrate the necessity of implementing preventive engineering solutions, including flow diversion dams and improved mine waste management practices, to mitigate debris flow risks. The significance of debris flow modeling in areas prone to natural calamities and mining activities is emphasized, offering a framework for enhancing geological hazard assessments and developing effective disaster mitigation strategies.
Keywords: Debris flow; Storm-generated Debris; geological risk assessment; hazard mitigation; mine waste management